Effectiveness of a Participatory Learning Program in Coronavirus Prevention for Vulnerable Muslim Women in Pak kret district, Nonthaburi province - Pinchaleaw, Duangkamol; Srisawad, Kanjana (Journal of The Royal Thai Army Nurses, 2025)
The purpose of this quasi-experimental research was to study the effects of a participatory learning program on self-awareness, knowledge and coronavirus 2019 preventive behaviors in vulnerable Muslim women, Pak Kret District, Nonthaburi Province. The sample included 40 Muslim women aged 18-59 years who had body mass index over standard, and they were divided into the experimental (20) and the comparison (20) groups. The research instruments included: 1) the participatory learning program which was developed based on the participatory learning concept of Kolb, with a duration of 6 weeks, and 2) questionnaires on general information, self-awareness, knowledge and coronavirus 2019 preventive behaviors. Content validity indexes (CVI) were .89–1.00, and the reliability scores were .78, .88, and .92, respectively. Data was analyzed by descriptive statistics and t-test. The result revealed as follows. 1) After attending the program, self- awareness and knowledge of the experimental group were not significantly different than before attending the program, and these results were not significantly different from the comparison group. 2) After attending the program, coronavirus 2019 preventive behaviors of the experimental group were significantly higher than before attending the program (p-value<.01), and were different from those of the comparison group, but not to a significant degree (p-value<.05).